Address to the Board of Governors, September 27, 1971 - McNamara, Robert S. (World Bank, Washington, DC, 2020)
Robert S. McNamara, President of the World Bank Group, remarked that progress has been made in both the qualitative and quantitative aspects of life in the vast majority of developing countries. Development has brought death rates down in those countries, but a corresponding adjustment in the birth rate is not automatic, and to date has been negligible. He focused on the basic problems of development: nutrition, employment, income distribution and trade.